2001
DOI: 10.1016/s0140-9883(00)00079-7
|View full text |Cite
|
Sign up to set email alerts
|

Chaos in oil prices? Evidence from futures markets

Abstract: We test for the presence of low-dimensional chaotic structure in crude oil, heating oil, and unleaded gasoline futures prices from the early 1980s. Evidence on chaos will have important implications for regulators and short-term trading strategies. While we find strong evidence of non-linear dependencies, the evidence is not consistent with chaos. Our test results indicate that ARCH-type processes, with controls for seasonal variation in prices, generally explain the non-linearities in the data. We also demons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
58
1

Year Published

2004
2004
2023
2023

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 116 publications
(60 citation statements)
references
References 40 publications
1
58
1
Order By: Relevance
“…Complementarily, a large body of literature suggests that crude oil prices have a statistically significant effect on economic activity (Adrangi, et al, 2001;Berument, et al, 2010;Brown & Yücel, 2001;Costantini & Martini, 2010;Fofana, et al, 2009;Hamilton, 2009aHamilton, , 2009bHanabusa, 2009;Hsing, 2007;Huang, et al, 1996;Jayaraman & Choong, 2009;Jiao & Ma, 2006;Jones, et al, 2004b;Odusami, 2010;Oladosu, 2009;Papapetrou, 2001;Rafiq, et al, 2009;Reynolds & Kolodziej, 2007;Zagaglia, 2010). Uri (1996) indicated the effect of changes in the price of crude oil on agricultural employment in the USA between 1947 and 1995 using Granger Causality.…”
Section: Literaturementioning
confidence: 99%
“…Complementarily, a large body of literature suggests that crude oil prices have a statistically significant effect on economic activity (Adrangi, et al, 2001;Berument, et al, 2010;Brown & Yücel, 2001;Costantini & Martini, 2010;Fofana, et al, 2009;Hamilton, 2009aHamilton, , 2009bHanabusa, 2009;Hsing, 2007;Huang, et al, 1996;Jayaraman & Choong, 2009;Jiao & Ma, 2006;Jones, et al, 2004b;Odusami, 2010;Oladosu, 2009;Papapetrou, 2001;Rafiq, et al, 2009;Reynolds & Kolodziej, 2007;Zagaglia, 2010). Uri (1996) indicated the effect of changes in the price of crude oil on agricultural employment in the USA between 1947 and 1995 using Granger Causality.…”
Section: Literaturementioning
confidence: 99%
“…Fig.2 shows elements of function (1). If max Lyapunov exponent of a data series is more than zero, then the data series has chaos characteristics.…”
Section:  Is the Maxmentioning
confidence: 99%
“…According to chaos theory and fractal theory, there is a relationship between history price series. To analyze this relationship, some reports had researched chaos mechanism of crude oil market [1], and others had try to model the mechanism of crude oil market [2] [3] [4].Forecasting is important purpose of those studies. Comparing to research by chaos theory [5] [6] [7] [8], some researches which modeling and forecasting crude oil market [9] [10], had utilized regression model, such as ARCH-type models [11].…”
Section: Introductionmentioning
confidence: 99%
“…Further, Alvarez et al (2008) showed in their research that the random walk-type behavior in energy futures prices, thus the autocorrelation in oil prices diminishes over time. Adrangi et al (2001) tested the presence of low-dimensional chaotic structure in crude oil, heating oil, and unleaded gasoline futures prices with their sample starting by the early 1980s. In their study, they pointed at chaotic structure and high persistence in the series investigated and concluded that chaotic structure and high persistence in the data would create strong implications for regulators and short-term trading strategies.…”
Section: Introductionmentioning
confidence: 99%